PENGARUH STRUKTUR KEPEMILIKAN, UMUR PERUSAHAAN, KOMITE AUDIT, DEWAN KOMISARIS TERHADAP AUDIT LAG - Sri Ayem; Reni Listyawati; Meydiana Rizka Nur Anggraeni (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
The phenomenon of audit report lag in Indonesia is not something new, apart from regulations regarding financial reporting, time discrepancies in submitting financial reports that have been audited are still found in many companies. The aim of this research was to investigate how ownership structure, company age, audit committee, and board of commissioners influence the delay in audit report submission. Secondary data was collected for this study. The population of interest comprised property and real estate companies that were listed on the IDX between 2018 and 2021. Classical assumption tests, multiple linear regression analysis, and hypothesis testing were employed for data analysis, utilizing the IBM SPSS 25 software. It was found that ownership structure, company age, audit committee, and board of commissioners had a detrimental impact on the timeliness of audit report submission.